(untitled) (Brazilian Geographical Journal, 2019)
This work analyzes the spatial distribution of the Brazilian caves by using geoprocessing techniques and associating these caves to different thematic maps. According to the Brazilian Center for Research and Conservation of Caves (CECAV) database, there are 16,089 known caves in Brazil. The spatial analysis of these caves was performed by combining their location with other information, such as the Brazilian states, biomes, drainage basins, geologic maps and potential data for the occurrence of more caves. In some regions, due to a large number of caves, the caves hid one another when represented by points by overlapping and could not be viewed on some maps. Therefore, the Kernel Density Estimation (KDE) technique was carried out to visualize regions based on their number of caves. All of these analyses were performed using the Geographical Information System (GIS) package ArcGIS v.10.3. The Brazilian states with the largest numbers of caves are Minas Gerais (6,301 caves - 39.16%) and Pará (2,473 caves - 15.37%). On the other hand, there are no known caves in Acre, the only state with no caves. Caves occur in all the Brazilian biomes and drainage basins, mainly in the Cerrado biome and in the São Francisco basin and are associated mainly with carbonate rocks and Banded Iron Formations (BIFs), but also occur in other lithologies, such as quartzites and sandstones. The potential map for the occurrence of caves, made based on the CECAV database, is also very helpful and shows us where else we may find more caves, so we can preserve them. This work will also serve as a contribution for a worldwide map of cave regions.